Ribonucleases - Nicholson, Allen W.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Ribonucleases are a ubiquitous and functionally diverse group of enzymes that have a common ability to cleave RNA. Either through scission of internal phosphodiesters, or removal of nucleotides from RNA 5' or 3' ends, ribonucleases perform essential roles in gene expression and regulation, genome replication and maintenance, host defense, stress response, and viral strategies of infection. Ribonucleases have also served as highly informative models to understand virtually every aspect of biomolecular structure and function. The fifteen chapters in this volume are written by recognized researchers in the field, and provide in-depth analyses of the major ribonuclease families. Particular focus is given to the relation of ribonuclease structure and mechanism to biological function, as well as ribonuclease dysfunction in certain disease states. Other topics include the evolutionary genetics and functional diversification of ribonucleases, engineered ribonucleases as anti-cancer agents, the mechanisms of action of artificial ribonucleases, and ribonucleases as models to understand protein folding and stability. This volume should serve as an essential reference for a broad range of researchers and educators with interests in RNA metabolism, enzymology, and gene regulation.
The Superfamily of Vertebrate Secreted Ribonucleases -- Vertebrate Secretory (RNase A) Ribonucleases and Host Defense -- Antitumor Ribonucleases -- RNase T2 family: enzymatic properties, functional diversity, and evolution of ancient ribonucleases -- Stress-induced Ribonucleases -- Viral RNase Involvement in Strategies of Infection -- 5?-3? exoribonucleases -- Structure and degradation mechanisms of 3? to 5? exoribonucleases -- The RNA exosomes -- The Metallo-?-Lactamase Family of Ribonucleases -- Ribonuclease III and the Role of Double-Stranded RNA Processing in Bacterial Systems -- Structure and function of RNase H enzymes -- Ribonucleoprotein Ribonucleases P and MRP -- Nonenzymatic and Metal-ion-dependent RNA Cleavage, and RNase Models -- Ribonucleases as Models for Understanding Protein Folding.
Electronic reproduction.
Keywords: Ribonucleases; Electronic books